Does Capital Structure Mediate on Business Innovation and Firm Sustainable Performance? - Zalaza Ceradhina Rahmadhani, Ary; Dewi Rosidi, Pasha; Agustia, Dian (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2023)
This study was conducted to prove whether the role of the company's capital structure can mediate the influence of business innovation on a company's finances. The data source used in this research originates from the company's annual financial report for 2017-2021. The sampling technique uses purposive sampling from the non-financial sector listed on the Indonesia Stock Exchange as of 2018; the sample data used was 1135 observations. The results show that capital structure mediates the relationship between investment opportunity set and financial performance. This is caused by increasing the investment opportunity set and making a good decision, which will impact appropriate capital structure decisions to support the company's operational activities. This explanation is by agency theory and pecking order theory. The results of this research can contribute to companies improving the effectiveness of business innovation decisions and capital structure to achieve optimal company financial performance.